2021
DOI: 10.1007/s00417-021-05348-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among total tear IgE, specific serum IgE, and total serum IgE levels in patients with pollen-induced allergic conjunctivitis

Abstract: Background Recently, the number of patients with pollinosis, particularly Japanese cedar pollinosis, has markedly increased. We previously reported about local allergic conjunctivitis, which is a phenotype of allergic conjunctivitis (AC). AC cases are often sensitized by various antigens. This study aimed to investigate the relationship among total tear IgE (t-tIgE), specific serum IgE (s-sIgE), and total serum IgE (t-sIgE) levels in patients with pollen-induced AC. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Recently, Yamana et al. 37 also found that pollen‐induced AC can be caused by pollen sensitization in the conjunctiva since pollen‐specific IgE antibodies have a higher total tear IgE positive rate than other antigens. This further confirms our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yamana et al. 37 also found that pollen‐induced AC can be caused by pollen sensitization in the conjunctiva since pollen‐specific IgE antibodies have a higher total tear IgE positive rate than other antigens. This further confirms our results.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this is because we analyzed the total IgE in tears and not specifically pollen IgE. Recently, Yamana et al 37 also found that pollen-induced AC can be caused by pollen sensitization in the conjunctiva since pollenspecific IgE antibodies have a higher total tear IgE positive rate than other antigens. This further confirms our results.…”
Section: The Change In Tear Ige Can Reflect the Evolution Of Disease ...mentioning
confidence: 98%
“…Generally, food allergy is an IgE-mediated type I hypersensitivity, which can induce immune cells to produce IgE antibodies [ 36 , 37 , 38 ]. Dot-blot assay was used to semi-quantitatively analyze the level of IgE antibodies in mice serum.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated serum and tear IgE levels can be demonstrated in approximately 78 and 96% of patients with SAC, respectively. 29 Elevated mite-specific serum IgE levels can be demonstrated in 89% of patients with PAC and 43% of patients with SAC. In tear film, mite-specific IgE can be detected in 78% of patients with PAC, but it is rarely present in those with SAC.…”
Section: Etiologymentioning
confidence: 99%
“…Eotaxin and thymus and activation-regulated chemokine (TARC) stimulate migration of eosinophil and Th2 cell from the circulation, respectively. 29,31 Patients with OA present with ocular and periocular pruritus, hyperemia, lacrimation, ocular foreign body sensation, sensitivity to light, and ocular secretions. Most of the time, symptoms are bilateral.…”
Section: Etiologymentioning
confidence: 99%